Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-91554-z
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of cadmium and lead in vegetables and fruits

Abstract: Chemical contamination of foods pose a significant risk to consumers. A source of this risk is due to the consumption of products contaminated with heavy metals such as cadmium (Cd) and lead (Pb). The aim of the study was to research the levels of Cd and Pb contamination of selected species of vegetables and fruits in the form of fresh, frozen, dried and processed products. The goal was to verify which of these food groups was more contaminated with heavy metals. The study covered 370 samples of fruits and veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 18 publications
(34 reference statements)
2
7
2
Order By: Relevance
“…Previously published data on As [34][35][36][37][38], Cd [36,37,[44][45][46][47], Pb [18,[35][36][37][44][45][46][47][48]54], and Zn [17,18,34,35,45,47,54,[57][58][59][60][61] are comparable to the findings from the present study. The results obtained are also comparable with previous research carried out on samples of fruits and vegetables from Romania [16,49,50] and Moldavia [38].…”
Section: Reduce Heavy Metals In Fruits and Vegetables By Soaking With...supporting
confidence: 91%
See 1 more Smart Citation
“…Previously published data on As [34][35][36][37][38], Cd [36,37,[44][45][46][47], Pb [18,[35][36][37][44][45][46][47][48]54], and Zn [17,18,34,35,45,47,54,[57][58][59][60][61] are comparable to the findings from the present study. The results obtained are also comparable with previous research carried out on samples of fruits and vegetables from Romania [16,49,50] and Moldavia [38].…”
Section: Reduce Heavy Metals In Fruits and Vegetables By Soaking With...supporting
confidence: 91%
“…The results obtained for Cd were comparable to those obtained by Rusin et al (2021) [44] (0.001-0.131 mg/kg fruit samples from Poland), Bagdatlioglu et al (2010) [45] (ND-0.024 µg/g vegetable samples from Turkey), Marín et al (2018) [36] (ND-0.0088 mg/kg vegetable and fruit samples from Spain), Shutian et al (2019) [37] (0.043 mg/kg chestnut samples from China), Zeiner et al (2018) [46] (Cd < 0.028 mg/kg d.w.), and Ferrante et al (2013) [47] (Cd < 0.004-0.71 µg/g fruit and vegetable samples from Italy). In a study by Antić-Mladevović et al ( 2009) [48], Cd levels in raspberry and blueberry samples from Montenegro (0.59-0.64 mg/kg DW) were significantly higher than those presented in this study.…”
Section: Cadmiumsupporting
confidence: 91%
“…The concentration of Pb in chard (0.563 µg g -1 ) and spinach (0.575 µg g -1 ) were lower than the concentration (46.24 and 10.29 µg g -1 ) reported previously in the study conducted by Mohamed et al (2003). The concentration of Pb in Egyptian leek (0.342 µg g -1 ) and spring onion (0.244 µg g -1 ) of this investigation were lower compared to the study performed by Naghipour et al (2018) which were 1.27 and 0.58 µg g -1 , respectively, while the concentration of Pb acquired in celery (1.323µgg -1 ) was higher than the result of Guerra et al (2012) and Rusin et al (2021) which were 0.47 µg g -1 and 0.259, respectively. Regarding garden cress, the concentration of Pb was 0.466 µg g -1 and lower than that gained by Souri et al (2018) which was 3.5 µg g -1 .…”
Section: Leadcontrasting
confidence: 75%
“…TheconcentrationsofCdinchard(0.054μgg −1 ), garden cress (0.224 μg g −1 ), spinach (0.182 μg g−1),Egyptianleek(0.059μgg −1 ), were lower than the concentrations (0.56 to 1.62 µg g -1 ) documented by Mohamed et al (2003) but higher than the concentration (0.04 µg g-1) reported by Bigdeli and Seilsepour, 2008). The Cd content in celery (0.329 μg g −1 ) obtained was greater than that documented (0.03 to 0.152 μg g −1 ) by Rusin et al (2021). The present concentration 0.224 µg g -1 of Cd evaluated in garden cress was lower than the value obtained by Bigdeli and Seilsepour (2008) which was 1.25 µg g -1 .…”
Section: Cadmiumcontrasting
confidence: 70%
“…There are also a number of reasons that could be related to loss of cells with speci c food types. Soft fruits and leafy vegetables can be of a more acidic nature and it has been shown that these food groups can be contaminated with heavy metals such as cadmium and lead (Rusin et al 2021). Pork sausage raw meat, pâté and cooked mussels contain high levels of fat (Online Resource 1), which also could contribute to cell death (Ebadi and Mazurak 2014).…”
Section: Summary and Discussionmentioning
confidence: 99%